Appropriate body mass index and waist circumference cutoff for overweight and central obesity among adults in Cambodia. - Yom An; Siyan Yi; Annette Fitzpatrick; Vinay Gupta; Piseth Raingsey Prak; Sophal Oum; James P Logerfo (PLoS ONE, 2013)
BACKGROUND: Body mass index (BMI) and waist circumference (WC) are used in risk assessment for the development of non-communicable diseases (NCDs) worldwide. Within a Cambodian population, this study aimed to identify an appropriate BMI and WC cutoff to capture those individuals that are overweight and have an elevated risk of vascular disease. METHODOLOGY/PRINCIPAL FINDINGS: We used nationally representative cross-sectional data from the STEP survey conducted by the Department of Preventive Medicine, Ministry of Health, Cambodia in 2010. In total, 5,015 subjects between age 25 and 64 years were included in the analyses. Chi-square, Fisher's Exact test and Student t-test, and multiple logistic regression were performed. Of total, 35.6% (n = 1,786) were men, and 64.4% (n = 3,229) were women. Mean age was 43.0 years (SD = 11.2 years) and 43.6 years (SD = 10.9 years) for men and women, respectively. Significant association of subjects with hypertension and hypercholesterolemia was found in those with BMI ≥ 23.0 kg/m(2) and with WC >80.0 cm in both sexes. The Area Under the Curve (AUC) from Receiver Operating Characteristic curves was significantly greater in both sexes (all p-values <0.001) when BMI of 23.0 kg/m(2) was used as the cutoff point for overweight compared to that using WHO BMI classification for overweight (BMI ≥ 25.0 kg/m(2)) for detecting the three cardiovascular risk factors. Similarly, AUC was also significantly higher in men (p-value <0.001) when using WC of 80.0 cm as the cutoff point for central obesity compared to that recommended by WHO (WC ≥ 94.0 cm in men). CONCLUSION: Lower cutoffs for BMI and WC should be used to identify of risks of hypertension, diabetes, and hypercholesterolemia for Cambodian aged between 25 and 64 years.